KONDISI EKOSISTEM TERUMBU KARANG DI PULAU PELAPIS, KAYONG UTARA - Dahlia Wulan Sari; Achis Martua Siregar; Herti Herawati (JURNAL BORNEO AKCAYA, 2023)
One of the coral reef ecosystems in West Kalimantan is located on Pelapis Island, North Kayong Regency. Coral reefs are coastal ecosystems with a high level of diversity but are vulnerable to various local and regional disturbances. Coral reef ecosystems are also a natural habitat for several types of marine biota. Coral reefs also play a role in coastal protection and provide services for tourism. The function of the coral reef ecosystem is highly dependent on the condition of the ecosystem. Therefore, research on the condition of coral reefs is substantial to study. Observations of coral reef ecosystems on Pelapis Island were carried out using Scuba at a depth of 5-7 m. Coral reef data collection was carried out using the Line Intercept Transect (LIT) method. Data on water conditions were obtained in situ and through analysis in the laboratory. The results showed that the waters on Pelapis Island were suitable for the growth of coral reefs. According to Minister of Environment Decree No. 4 of 2001, the coral reef ecosystem at station 2 was included in the good category and moderately damaged category at station 1 with a percentage of coral cover of 62.82% and 42.13%, respectively. Hard corals at both locations were dominated by massive coral (CM). The data obtained can be one of the references in regional management and sustainable use of marine space